The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31557/apjcp.2021.22.12.4037
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Response to Erythropoiesis Stimulating Agents in Low-Risk Myelodysplastic Syndromes

Abstract: The natural history and prognosis of MDS are classified by the International Prognostic Scoring System (IPSS) and Revised International Prognostic Scoring System (R-IPSS). In low-risk MDS (low or intermediate-1 IPSS or R-IPSS ≤ 3.5), anemia is the predominant feature, often leading to red blood cell (RBC) transfusion requirement, poor quality of life, and worsening cardiovascular comorbidities (Steensma and Bennett, 2006). Correcting anemia by transfusion support or enhancing intrinsic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, based on the quantitative associations with response, the general consensus followed that 'responders' had higher baseline hemoglobin levels than 'non-responders'. In four studies [26,36,39,52], this relationship was statistically significant, and in another four studies, it did not show statistical significance [30,45,46,50]. Moreover, in two other studies, 'responders' had lower median or mean hemoglobin levels than 'non-responders'; however, neither of these studies reported statistical significance [29,56].…”
Section: Hemoglobin Levelsmentioning
confidence: 83%
See 4 more Smart Citations
“…However, based on the quantitative associations with response, the general consensus followed that 'responders' had higher baseline hemoglobin levels than 'non-responders'. In four studies [26,36,39,52], this relationship was statistically significant, and in another four studies, it did not show statistical significance [30,45,46,50]. Moreover, in two other studies, 'responders' had lower median or mean hemoglobin levels than 'non-responders'; however, neither of these studies reported statistical significance [29,56].…”
Section: Hemoglobin Levelsmentioning
confidence: 83%
“…However, the general consensus among them was that 'responders' had lower mean or median ferritin levels than 'non-responders'; in three studies [39,46,48], this relationship was statistically significant. In another three studies, it was not statistically significant [28,33,50]. Moreover, in one French study, 'responders' had higher median ferritin levels than 'non-responders' but did not report statistical significance [26].…”
Section: Serum Ferritin Levelsmentioning
confidence: 88%
See 3 more Smart Citations